Lochinvar luck. - Terhune, Albert Payson, 1872-1942. (New York, Grosset & Dunlap, 1961)
A year in the wild turns a scrawny, runty collie pup into the pedigree beauty who wins ribbons and displays the loyalty expected of his line.
Keywords: Dogs -- Juvenile fiction; Dogs -- Fiction